Die Johannese Logos kom opnuut tuis in Afrika - Du Rand, Jan A. (Verbum et ecclesia, 2002)
The Johannine Logos once again comes home in Africa In many parts of Africa people are still staggering under the burden of colonialism, civil wars, illnesses, drought, famine, poverty and corruption, to name but a few. On the other hand, one should also take notice of the warmth of its variety of peoples, the family and community values and the promotion of mutual care. Who is Jesus in the midst of all this? Jesus has many faces in Africa, like being the master of initiation, the chief, the ancestor and elder brother, the healer and the liberator from suffering, to name some.